STRATEGI PENGEMBANGAN UMKM BERBASIS PANGAN LOKAL DI KECAMATAN TANA LILI KABUPATEN LUWU UTARA - Khumaera, Nur Ifra (Berkala Ilmiah AGRIDEVINA, 2020)
Agricultural resources are very large in North Luwu Regency, so it is very potential to be developed especially in the form of local food preparations by the SMEs. However, the ability of MSMEs in developing their businesses is not optimal because of the limited market reach. This study aims to determine (1) internal and external environmental analysis in Local Food Based MSMEs, (2) strategies for developing local food based MSMEs. This research was conducted in Tana Lili Subdistrict, North Luwu Regency. Analysis of the data used in this research is descriptive and SWOT analysis. The population and sample in this study were drawn from SMEs, consumers and stakeholders related to the total number of 37 respondents. The results of this study indicate that strategies that can be carried out in developing local food-based MSMEs in the Tana Lili Subdistrict are: (1) utilizing labor from the environment to increase production, (2) increasing production of local processed food products, (3) conducting training for owners business and workforce to develop business, (4) optimize product promotion through internet media and brochures, (5) maintain product taste and improve product quality in order to compete with other products, (6) create new innovations that are more attractive, (7) increasing distributor power to minimize the potential for new competitors and changes in lifestyle and consumption patterns of the community. The results of this study can be used as a reference by SMEs and stakeholders in designing and developing the potential of MSMEs in Tanalili District, North Luwu Regency, South Sulawesi. DOI : https://doi.org/10.33005/adv.v9i1.2209